The Hidden Costs of Downsizing - Matthias Heinz; Frank Drzensky (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze whether a principal s decision to layoff an agent affects the performance of the surviving agents. To study the impact of the decision in isolation, we conducted an experimental principal-agent game. We find that agents reduce their performance by 37% as a response to the decision. Heterogeneity in principals decisions can largely be explained by different beliefs about how agents react to layoffs.
Keywords: J63; C91; J82; 330